Risk of surgical site infections after colorectal surgery and the most frequent pathogens isolated: a prospective single-centre observational study - George Panos; Francesk Mulita; Karolina Akinosoglou; Elias Liolis; Charalampos Kaplanis; Levan Tchabashvili; Michail Vailas; Ioannis Maroulis (Medicinski glasnik, 2021)
Aim: To identify risk factors for developing surgical site infections (SSIs) based on a prospective study of patients undergoing colorectal surgery. Methods: Between November 2019 and January 2021, 133 patients underwent elective operation for colorectal cancer in our institution. The following variables were recorded for each patient: age, gender, body mass index (BMI), American Society of Anesthesiologists Classification (ASA class), duration of surgery, wound classification, skin preparation regimens, surgical approach, comorbidities (hypertension, diabetes, cardiovascular disease, respiratory disease, chronic steroid use), and pathogens responsible for surgical site infection. Univariate analysis was performed using χ2 tests for categorical variables. Results: A total of 65 males and 68 females were enrolled. Postoperative SSI was diagnosed in 29 (21.8%) cases. Fifty five patients were >70 years old, and SSIs were significantly more frequent in this group (p=0.033). There were 92 patients with BMI <30kg/m2 and 87 with ASA class ?2; SSIs occurred significantly less frequently in these patients (p=0.021 and p=0.028, respectively). Open surgery was performed in 113 patients; 35 (out of 113; 31%) wound infections were classified as contaminated or dirty, and SSI occurred more often in these two groups (p=0.048 and p=0.037, respectively). Nineteen patients had diabetes and 36 used steroids continuously; SSI was significantly more frequent in these patients (p=0.021 and p=0.049, respectively). Conclusion: Following colorectal cancer procedures SSIs were significantly more common among patients over 70 years old, BMI?30kg/m2, ASA score>2, with diabetes and chronic steroid use, undergoing open, dirty or contaminated surgery. Escherichia coli and Enterococcus spp. were the two most common pathogens isolated.
Keywords: colorectal cancer; microorganism; risk factor; wound infection